Hypnosis and Dyspareunia: A Meta Analysis - Kumalasari, Ratna Dewi; Tamtomo, Didik Gunawan; Prasetya, Hanung (Indonesian Journal of Medicine, 2020)
Background: Sexual satisfaction refers to a person's pleasant feelings from the type of sexual relationship that forms an important part of one partner's impression of another. 75% of women experience sexual problems. Symptoms of sexual dysfunction occur in nearly half of the marriage period and 75% of couples need therapy. This study aims to analyze the effect of hypnosis on pain during sexual activity and the intensity of pain.Subjects and Method: This study was a meta-analysis and a systematic study. The articles used were obtained from several electronic databases including Pubmed, Science Direct, Springer Link, and Google Scholar. Articles were collected for 4 weeks. The keywords to search for articles were as follows: "non-medical therapy", "non-medical care", "randomized control trial", "sexual disturbance", "sexual function", "sexual satisfaction". The articles studied were full text articles with an observational research design. Articles were collected using PRISMA diagrams, and analyzed using the Review Manager 5.3 application.Results: The effects of hypnosis on pain during sexual activity (aOR= 3.55; 95% CI= 2.63 to 4.79; p = 0.001) and intensity of pain (aOR=  2.39; 95% CI= 1.96 to 2.82; p= 0.006).Conclusion: Hypnosis can reduce pain during sexual activity and the intensity of pain.Keywords: Hypnosis, sexual dysfunctionCorrespondence: Kumalasari. Masters Program in Public Health Sciences, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: logicakinanthi@gmail.com. Mobile: +62812623900900.Indonesian Journal of Medicine (2020), 05(04): 291-298https://doi.org/10.26911/theijmed.2020.05.04.04.